الموظفون الخاضعون لتقارير تقييم الأداء الوظيفي في القانون الفلسطيني "دراسة مقارنة" - محمود الجمالي, أ/ حـازم حمدي (Sciences humaines, 2015)
هدفت الدراسة إلى التعرف    على الموظفين الخاضعين لتقارير تقييم الأداء الوظيفي في القانون الفلسطيني، حيث نهجت الدراسة المنهج الوصفي التحليلي، والمنهج المقارن، واعتمدت على المصادر الثانوية للحصول على المعلومات. وتوصلت الدراسة إلى كثير من النتائج من أهمها:إن جميع الموظفين في دول القانون المقارن -وإن اختلفت فئاتهم ودرجاتهم -يخضعون لنظام تقارير تقييم الأداء الوظيفي، وأوصت الدراسة بضرورة وجود نظام يلزم الرئيس بمناقشة مرؤوسيه عن أدائهم، واطلاعهم على نقاط القوة والضعف في هذا الأداء، والعمل على تنمية نقاط القوة، وعلاج نقاط الضعف.   The study titled "Employees Subjected to Reports of Job Performance Evaluation and in the Palestinian law. Comparative study”, aimed to indentify the employees/staff who are subjected to the reports of job performance evaluation, and the competent authority in conducting the evaluation according to the Palestinian law.The study utilized the descriptive, analytical approach, and comparative approach. It depended on secondary resources in getting the information.The study achieved many results the most important results are show that, the majority of the employees in the comparative law countries, regardless of their categories and grades, were subjected to job performance evaluation system. In addition, the results The study recommended that, there must be a law that requires the president to discuss his subordinates/employees for their performance and inform them of points of strengths and weaknesses of their performance. He should work on enhancing and developing points of strengths and find solutions to points of weaknesses.